Pengaruh Motivasi dan Efikasi Diri terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Aceh - Arinal Haqqi; Agus Ariyanto; M.Yamin (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Entrepreneurial interest among university students is a strategic factor in driving economic growth and expanding job opportunities. However, not all students share a strong interest in entrepreneurship. One of the main reasons is the low level of motivation and self-efficacy. This study aims to examine the extent to which motivation and self-efficacy affect students’ entrepreneurial interest. The research method employed was a quantitative approach with an associative design to analyze the relationship between variables. The population consisted of all active undergraduate students of the Faculty of Economics, Muhammadiyah University of Aceh, enrolled in the Even Semester of the 2022 cohort, totaling 1,350 students. The sample was determined using Slovin’s formula, resulting in 93 respondents. They were selected randomly, or through incidental sampling, by inviting students willing to complete a Google Form and provide their WhatsApp numbers. The findings indicate that both motivation (X1) and self-efficacy (X2) have a positive and significant effect on entrepreneurial interest (Y), both partially and simultaneously.